Activation of neurons in the insular cortex and lateral hypothalamus during food anticipatory period caused by food restriction in mice - Jihao Ma; Sakurako Yanase; Lisa Udagawa; Tomoyuki Kuwaki; Ikue Kusumoto-Yoshida (Journal of Physiological Sciences, 2023)
Abstract Mice fed a single meal daily at a fixed time display food anticipatory activity (FAA). It has been reported that the insular cortex (IC) plays an essential role in food anticipation, and lateral hypothalamus (LH) regulates the expression of FAA. However, how these areas contribute to FAA production is still unclear. Thus, we examined the temporal and spatial activation pattern of neurons in the IC and LH during the food anticipation period to determine their role in FAA establishment. We observed an increase of c-Fos-positive neurons in the IC and LH, including orexin neurons of male adult C57BL/6 mice. These neurons were gradually activated from the 1st day to 15th day of restricted feeding. The activation of these brain regions, however, peaked at a distinct point in the food restriction procedure. These results suggest that the IC and LH are differently involved in the neural network for FAA production.